Hubungan Lama Pemakaian Suntik DMPA dengan Penurunan Libido pada Akseptor Suntik DMPA di Praktik Mandiri Bidan Hana Sri Wuryaningsih Parakan: Relationship of Duration of Use with Decreased Libido in DMPA Injectable KB Acceptors at PMB Hana Sri Wuryaningsih Parakan - Hana Sri Wuryaningsih; Riska Ismawati Hakim; Dian Monalisa Rusliani (Journal of Health, 2025)
Long-term use of Medroxy Progesterone Acetate (DMPA) Injectable Contraceptives can lower estrogen levels, affect hormone metabolism, and reduce serum estradiol content, resulting in a decrease in women's sexual function. DMPA Injectable Birth Control shows significant sexual dysfunction effects if used for more than 2 years. This study aims to determine the relationship between the long use of DMPA injections and the decrease in libido in DMPA injection acceptors at PMB Hana Sri Wuryaningsih. The research design uses a correlative descriptive approach with a cross sectional approach. The population in this study is all acceptors of DMPA Injection Family Planning at PMB Hana Sri Wuryaningsih as many as 141 people. The sampling technique uses Purposive sampling. The number of samples was 104 respondents. This research instrument uses a questionnaire. Univariate analysis with frequency distribution table and bivariate analysis with Chi Square test. Respondents aged 21-35 years were 68 respondents (65.4%). Respondents who have children ≤ 2 amounted to 87 respondents (83.7%). Acceptors with >2 years of use amounted to 69 respondents (66.3%). The acceptors who experienced a decrease in libido amounted to 28 respondents (26.9%). Respondents who use DMPA injection >2 years have decreased, namely 25 respondents (24.0%). The Odds Ratio (OR) value is 6.061. The p value of 0.003 < 0.05 stated that there was a relationship between the long use of DMPA injection and a decrease in libido in DMPA injection acceptors at PMB Hana Sri Wuryaningsih.